PENGARUH MODEL CTL BERBASIS KEARIFAN LOKAL TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN IPAS SDN GANDEKAN SURAKARTA - Yunita Sari, Vina; Trisiana, Anita; Jumanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Addressing the challenges of the 21st century requires the mastery of critical thinking skills as a core competency. However, interviews and observations conducted by the researchers with both teachers and students revealed that students' critical thinking abilities remain relatively low. This is evident in their limited capacity to comprehend information, analyze problems, evaluate situations, and formulate appropriate solutions. Furthermore, the teaching methods used are still traditional and do not integrate subject matter with local contexts relevant to students’ daily lives. This study aimed to examine the effect of implementing the Contextual Teaching and Learning (CTL) model, incorporating local wisdom, on the critical thinking skills of fourth-grade students in Integrated Science and Social Studies (IPAS) at SDN Gandekan Surakarta, consisting of 25 students. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The findings showed a significant difference in students’ critical thinking skills before and after the application of the CTL model with a local wisdom approach. A paired sample t-test yielded a two-tailed significance value of 0.000 (p < 0.05), indicating that the intervention had a statistically significant impact. The average test scores increased from 61.68 (pretest) to 82.12 (posttest), and the average questionnaire score rose from 52.80% to 81.40%. These results suggest that the implementation of the Contextual Teaching and Learning (CTL) model based on local wisdom effectively enhances students’ critical thinking skills in Integrated Science and Social Studies (IPAS) learning.